Use and cost comparison of clobazam to other antiepileptic drugs for treatment of Lennox-Gastaut syndrome. Issue 1 (1st January 2017) - François, Clément; Stern, John M.; Ogbonnaya, Augustina; Lokhandwala, Tasneem; Landsman-Blumberg, Pamela; Duhig, Amy; Shen, Vivienne; Tan, Robin
ABSTRACT: Background : Lennox-Gastaut syndrome (LGS) is a severe form of childhood-onset epilepsy associated with serious injuries due to frequent and severe seizures. Of the antiepileptic drugs (AEDs) approved for LGS, clobazam is a more recent market entrant, having been approved in October 2011. Recent AED budget impact and cost-effectiveness analyses for LGS suggest that adding clobazam to a health plan formulary may result in decreased medical costs; however, research on clinical and economic outcomes and treatment patterns with these AED treatments in LGS is limited. Objectives : To compare the baseline characteristics and treatment patterns of new initiators of clobazam and other AEDs among LGS patients and compare healthcare utilization and costs before and after clobazam initiation among LGS patients. Methods : A retrospective study of probable LGS patients was conducted using the MarketScan® Commercial, Medicare Supplemental, and Medicaid databases (10/1/2010-3/31/2014). Results : In the Commercial/Medicare Supplemental population, clobazam users were younger, had fewer comorbidities, and more prior AED use than non-clobazam users. In the 12 months pre-treatment initiation, clobazam users had significantly more seizure-related inpatient stays and outpatient visits and higher total seizure-related ( P < 0.001) and all-cause ( P < 0.001) costs than non-clobazam users. Among clobazam users, when compared to the 12 months pre-clobazam initiation, seizure-related medical utilization and costs were lower in the 12 months post-clobazam initiation ( P = 0.004). Total all-cause ( P < 0.001) and seizure-related ( P = 0.029) costs increased post-clobazam initiation mainly due to the increase in outpatient pharmacy costs. Similar results were observed in the Medicaid population. Conclusions : Baseline results suggest a prescribing preference for clobazam in severe LGS patients. Clobazam users had a reduction in seizure-related medical utilization and costs after clobazam initiation. The improvement in medical costs mostly offset the higher prescription costs following clobazam initiation.